Swedish Plectida (Nematoda). Part 4. The genus Leptolaimus de Man, 1876 - Holovachov, Oleksandr; Boström, Sven (Zootaxa, 2013)
Twelve known and nine new species of Leptolaimus are described from bottom sediments collected in marine habitats of Sweden, including the Bothnian Sea and Bothnian Bay, the Baltic Sea proper, Gullmarn Fjord and the Skagerrak. Three of these species have been previously recorded in Sweden while nine are new records for the Swedish fauna. The following known species are redescribed: Leptolaimus papilliger de Man, 1876, L. cupulatus Lorenzen, 1972, L. danicus Jensen, 1978, L. donsi (Allgén, 1946) comb. n., L. mixtus Lorenzen, 1972, L. pellucidus (Southern, 1914) comb. n., L. venustus Lorenzen, 1972, L. lorenzeni (Boucher & de Bovée, 1972) comb. n., L. alatus Vitiello, 1971, L. macer Lorenzen, 1972, L. septempapillatus Platt, 1973, L. elegans (Schuurmans Stekhoven & De Coninck, 1933) Gerlach, 1958. Leptolaimus primus sp. n. is characterised by the 319–472 µm long body; rounded labial region continuous with body contour; cephalic setae 1.5–2.0 µm long; amphid located 7.0–11.5 µm from anterior end; first body pore located 18.5–28.0 µm from anterior end; lateral field originating 35 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male without tubular and with four alveolar supplements, alveolar supplements without sclerotized inner ring; spicules arcuate and 13.5–16.0 µm long. Leptolaimus secundus sp. n. is characterised by the 576–645 µm long body; rounded labial region continuous with body contour; cephalic setae 2.0 µm long; amphid located 6.5–7.0 µm from anterior end; first body pore located 23.0–28.5 µm from anterior end; lateral field originating 18.0–23.0 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male with single tubular and 9–15 alveolar supplements, tubular supplement weakly arcuate with blunt tips, alveolar supplements with sclerotized lining; spicules arcuate and 23.0–26.5 µm long. Leptolaimus tertius sp. n. is characterised by the 576–579 µm long body; rounded labial region continuous with body contour; cephalic setae 2 µm long; amphid located 4–5 µm from anterior end; first body pore located 21.0–23.5 µm from anterior end; lateral field originating 26–29 µm from anterior end; male with four tubular and 7–10 alveolar supplements, tubular supplements weakly arcuate with blunt tips, alveolar supplements with sclerotized inner ring; spicules arcuate and 25–26 µm long. Leptolaimus quartus sp. n. is characterised by the 597–686 mm long body; rounded labial region continuous with body contour; cephalic setae 2.0–3.5 µm long; amphid located 5.0–7.0 µm from anterior end; first body pore located 23.5–27.0 µm from anterior end; lateral field originating 19.0–27.0 µm from anterior end; male with three tubular and 8–9 alveolar supplements, tubular supplements straight with blunt expanded tips, alveolar supplements with sclerotized inner ring; spicules arcuate and 23.0–25.0 µm long. Leptolaimus quintus sp. n. is characterised by the 443–528 µm long body; rounded labial region continuous with body contour; cephalic setae 1.0–2.0 µm long; amphid located 7.0–10.0 µm from anterior end; first body pore located 18.0–28.5 µm from anterior end; lateral field originating 25.0–41.0 µm from anterior end; female with two tubular supplements (one just posterior to cardia and one in front of anus), vagina without pars refringens, vulva right-sublateral; male with 8–10 tubular and without alveolar supplements, tubular supplements weakly arcuate with anchor-like tips; spicules arcuate and 17.0–22.0 µm long. Leptolaimus sextus sp. n. is characterised by the 626–728 µm long body; truncated labial region offset from body contour; cephalic setae 1.5–2.0 µm long; amphid located 8.0–12.0 µm from anterior end; first body pore located 41.0–48.5 µm from anterior end; lateral field originating 28.0–41.0 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male with five (rarely six) tubular and without alveolar supplements, tubular supplements weakly S-shaped with bifid tips; spicules arcuate and 39.0–46.0 µm long. Leptolaimus septimus sp. n. is characterised by the 679–850 µm long body; truncate labial region offset from body contour; cephalic setae 2.5–3.5 µm long; amphid located 8.5–11.5 µm from anterior end; first body pore located 37.0–44.0 µm from anterior end; lateral field originating 26.5–37.0 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male with four (rarely five) tubular and without alveolar supplements, tubular supplements weakly S-shaped, with bifid or blunt tips; spicules arcuate and 31.0–33.5 µm long. Leptolaimus octavus sp. n. is characterised by the 541–638 µm long body; truncate labial region continuous with body contour; cephalic setae 1.5–2.0 µm long; amphid located 8.5–12.0 µm from anterior end; first body pore located 31.5–41.0 µm from anterior end; lateral field originating 26.0–40.0 µm from anterior end and expanding into bursa-like structures along the tail; female without supplements, vagina without pars refringens, vulva midventral; male with four tubular and without alveolar supplements, tubular supplements weakly S-shaped with dentate tips; spicules arcuate and 30.0–31.5 µm long. Leptolaimus nonus sp. n. is characterised by the 403–633 µm long body; rounded labial region continuous with body contour; cephalic setae 1.5–3.0 µm long; amphid located 8.0–10.0 µm from anterior end; first body pore located 16.5–29.0 µm from anterior end; lateral field originating 47.0–99.0 µm from anterior end and expanding into bursa-like structures along the proximal part of the tail; female without supplements, vagina with bacilliform pars refringens, vulva right-subventral; male with 4–5 tubular and without alveolar supplements, tubular supplements weakly arcuate with dentate tips; spicules arcuate and 17.0–26.0 µm long. The following nomenclatorial changes are proposed: Eutelolaimus donsi Allgén, 1947 is transferred to the genus Leptolaimus, as L. donsi (Allgén, 1947) comb. n.; Halaphanolaimus cangionensis Gagarin & Nguyen Vu Thanh, 2007 is transferred to the genus Leptolaimus, as L. cangionensis (Gagarin & Nguyen Vu Thanh, 2007) comb. n.; Halaphanolaimus harpaga Boucher & de Bovée, 1972 is transferred to the genus Leptolaimus, as L. harpaga (Boucher & de Bovée, 1972) comb. n.; Halaphanolaimus lorenzeni Boucher & de Bovée, 1972 is transferred to the genus Leptolaimus, as L. lorenzeni (Boucher & de Bovée, 1972) comb. n.; Halaphanolaimus pellucidus Southern, 1914 is transferred to the genus Leptolaimus, as L. pellucidus (Southern, 1914) comb. n.; Halaphanolaimus rivalis Gagarin & Nguyen Vu Thanh, 2007 is transferred to the genus Leptolaimus, as L. rivalis (Gagarin & Nguyen Vu Thanh, 2007) comb. n.; Halaphanolaimus marinus Kamran, Nasira & Shahina, 2010 is transferred to the genus Leptolaimus as L. marinus (Kamran, Nasira & Shahina, 2010) comb. n. and considered a junior synonym of Leptolaimus rivalis (Gagarin & Nguyen Vu Thanh, 2007) comb. n.; Halaphanolaimus sergeevae Ürkmez & Brennan, 2013 is transferred to the genus Leptolaimus as L. sergeevae (Ürkmez & Brennan, 2013) comb. n.; Leptolaimus vitielloi nom. nov. is proposed for Leptolaimus minutus Vitiello, 1971 nec L. minutus (Schuurmans Stekhoven, 1942) comb. n.; Polylaimium exile Cobb, 1920 is transferred to the genus Leptolaimus, as L. exilis (Cobb, 1920) comb. n. and is considered species inquirendae. A taxonomic review, tabular compendium and identification key for species of the genus Leptolaimus are also given.